Â¬Kajian kelayakan lokasi budidaya sidat (Anguilla spp.) di Perairan Danau Tondano, Provinsi Sulawesi Utara - Parenta, Villy D.; Pangemanan, Novie P. L.; Longdong, Sammy N. J.; Kusen, Diane J.; Salindeho, Indra R. N.; Tumembouw, Sipriana S. (e-Journal BUDIDAYA PERAIRAN, 2021)
The objective of this research was to determine feasibility ility on eel fish (Anguilla spp.) culture locations in Tondano Lake, North Sulawesi Province in terms of water quality, both physical and chemical parameters of the waters. Determination of the sampling point is placed at three predetermined points, station I located at Eris Village, Station 2 located at Paleloan Village and Station 3 located at Paslaten Village. The results showed that the waters of Lake Tondano have three classes of suitability for the location of eel (Anguilla spp.) culture, that is very suitable (S1), suitable (S2), and not suitable. Station I of Eris Village included in the suitable class (S2), Station II at Paleloan Village is included in the very appropriate very suitable class (S1), while Station III at Paslaten Village included in the class that is not suitable to be used as a location for eel culture in terms of water quality